The 20th Asia and South Pacific Design Automation Conference 2015
DOI: 10.1109/aspdac.2015.7059067
|View full text |Cite
|
Sign up to set email alerts
|

Toward large-scale access-transistor-free memristive crossbars

Abstract: Abstract-Memristive crossbars have been shown to be excellent candidates for building an ultra-dense memory system because a per-cell access-transistor may no longer be necessary. However, the elimination of the access-transistor introduces several parasitic effects due to the existence of partially-selected devices during memory accesses, which could limit the scalability of access-transistor-free (ATF) memristive crossbars. In this paper we discuss these challenges in detail and describe some solutions addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Unit RS memory cells should be integrated in a crossbar‐structured parallel matrix with bit and word line interconnections to realize a resistive random access memory (RRAM) for fully functional memory operations . In this case, it is crucial to minimize the leakage current flowing through neighboring cells since this causes undesirable electrical interference, readout margin degradation, and additional power consumption . Merced‐Grafals et al demonstrated the 1 transistor‐1 resistor (1 T‐1 R) array of TaO x ‐based memristors.…”
Section: Inorganic Resistive Switching Memoriesmentioning
confidence: 99%
“…Unit RS memory cells should be integrated in a crossbar‐structured parallel matrix with bit and word line interconnections to realize a resistive random access memory (RRAM) for fully functional memory operations . In this case, it is crucial to minimize the leakage current flowing through neighboring cells since this causes undesirable electrical interference, readout margin degradation, and additional power consumption . Merced‐Grafals et al demonstrated the 1 transistor‐1 resistor (1 T‐1 R) array of TaO x ‐based memristors.…”
Section: Inorganic Resistive Switching Memoriesmentioning
confidence: 99%
“…From Figure 2 we could extract the minimum voltage amplitude, V abs , able to achieve a correct writing operation within t op s for all working temperatures within the considered range. Should there not be any non-desirable counter effects [25], the voltage amplitude V a bs could be employed satisfying the writing requirements in the whole temperature range. However, using V a b s as writing amplitude no matter the circuit temperature would raise two major disadvantages: not only would the power consumption be increased, but also the use of an amplitude larger than the required would lead to behavioral problems.…”
Section: Overcoming Rram System Limitationsmentioning
confidence: 99%
“…Lithography and leakage-limited physical scaling and material dependent read/write voltage of electrical scaling are some of the issues plaguing today's non-volatile memories (NVMs) [1]. In recent years, several emerging memory technologies such as ReRAM [2,17], phase change memories [3], and spin-transfer torque magneto-resistive memories [4] have been under study to overcome these issues and Memristor technology has shown a lot of potential as a candidate for the next generation of non-volatile memory. Rather than replacing CMOS with these nascent technologies, a symbiotic approach utilizing the favorable properties of memristive devices, such as high density, fast switching and high endurance [5], could extend nanoscale memories beyond their current limitations.…”
Section: Introductionmentioning
confidence: 99%